Beyond the „repressive hypothesis”. Relations between drives and culture in Freud’s late psychoanalytic theory - Grzybowski, Antoni (Hybris, 2020)
The purpose of the article is to demonstrate that Freud's theory in its late, mature form significantly goes beyond the model associated with the "repressive hypothesis" and thus can potentially be a useful conceptual tool for analyzing the contemporary non-repressive society and the form of subjectivity it creates. To this end, an outline of the development of the Freudian psychoanalytic theory will be presented in relation to the "repressive hypothesis" from the early period of his work, and then move on to the mature work of Freud to discuss its most important elements such as the concept of narcissism, reformulation of the relationship between anxiety and repression and the concept of duality of life and death drives.